2018
DOI: 10.1038/s41598-018-31063-8
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms and health-related quality of life in Japanese patients with primary biliary cholangitis

Abstract: Although patients with primary biliary cholangitis (PBC) experience a variety of symptoms that could impair health-related quality of life (HRQOL), no studies regarding symptoms and impact of PBC on HRQOL have been performed in Asian countries. Herein, we aimed to evaluate symptoms and HRQOL in Japanese PBC patients. We performed a multicenter, observational, cross-sectional study. The PBC-40 and the short form (SF)-36 were used as measures of symptoms and HRQOL. Four-hundred-ninety-six patients with PBC were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 31 publications
4
22
0
1
Order By: Relevance
“…Inflammation is associated with decreased levels of albumin which may partly rebut the theory of an inflammatory aetiology of uraemic itch . Interestingly, a lower serum albumin was associated with itch scores in Japanese patients with biliary cholangitis …”
Section: Discussionsupporting
confidence: 91%
“…Inflammation is associated with decreased levels of albumin which may partly rebut the theory of an inflammatory aetiology of uraemic itch . Interestingly, a lower serum albumin was associated with itch scores in Japanese patients with biliary cholangitis …”
Section: Discussionsupporting
confidence: 91%
“…In PSC, no medical treatment has been shown to be effective in the improvement of LT‐free survival . Furthermore, even if responses to treatment are excellent, patients with AILD frequently experience a variety of physical symptoms and psychological problems such as fatigue, pruritus, abdominal pain, and psychological anxiety, significantly reducing health‐related quality of life …”
Section: Introductionmentioning
confidence: 99%
“…3 Furthermore, even if responses to treatment are excellent, patients with AILD frequently experience a variety of physical symptoms and psychological problems such as fatigue, pruritus, abdominal pain, and psychological anxiety, significantly reducing health-related quality of life. [4][5][6][7][8] Estimation of prevalence of AILDs is critical to assess the burden of these diseases on public health. A number of epidemiological studies have been undertaken for AIH, [9][10][11][12][13][14][15][16][17][18][19] PBC, 13,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] and PSC [37][38][39][40][41][42][43] worldwide, and have shown that prevalence significantly varies depending on regions and ethnicities.…”
Section: Introductionmentioning
confidence: 99%
“…Health-related quality of life (HRQoL) is an academic discipline, and it has become a fast-growing medical discipline widely accepted by governments, agencies, and public health departments [1,2].…”
Section: Introductionmentioning
confidence: 99%